Relevansi Hukum Perdata Klasik dalam Menjawab Sengketa Perjanjian Digital Masa Kini - Syahrial Adam; Nurmala Sari; Ahyar Rosidi (SIMPUL: Jurnal Ilmu Politik dan Hukum, 2025)
The development of digital technology has transformed the way agreements are formed, implemented, and disputed. Digital agreements present conceptual and practical challenges for civil law, particularly regarding validity, proof of intent, and the responsibilities of the parties. This study aims to analyze the relevance of classical civil law in addressing today's digital agreement disputes. The main focus of the study is directed at the role of classical civil law principles and constructions as a normative framework in assessing contractual relationships arising from electronic transactions. This study uses normative legal research methods with conceptual, statutory, and comparative approaches. The analysis is conducted on classical civil law principles, such as consensualism, freedom of contract, pacta sunt servanda, and good faith, and their application in the context of digital agreements, including electronic contracts, electronic signatures, smart contracts, and digital dispute resolution mechanisms. The legal materials are analyzed qualitatively through deductive and interpretive reasoning. The results of the study indicate that classical civil law remains relevant and operational in addressing digital agreement disputes. The legal requirements of classical agreements remain the main benchmark in assessing the validity of electronic contracts. The theory of will and the principle of good faith has been proven to explain and evaluate the process of forming and implementing digital agreements. Digitalization does not eliminate civil liability, but requires adjustments in the provision of evidence and the interpretation of norms. This study concludes that an integrative approach that maintains classical civil law as a normative foundation is an effective strategy for ensuring legal certainty and contractual justice in the digital era.